2002
DOI: 10.5483/bmbrep.2002.35.3.302
|View full text |Cite
|
Sign up to set email alerts
|

A Product Inhibition Study on Adenosine Deaminase by Spectroscopy and Calorimetry

Abstract: Kinetic and thermodynamic studies have been made on the effect of the inosine product on the activity of adenosine deaminase in a 50 mM sodium phosphate buffer, pH 7.5, at 27 o C using UV spectrophotometry and isothermal titration calorimetry (ITC). A competitive inhibition was observed for inosine as a product of the enzymatic reaction. A graphical-fitting method was used for determination of the binding constant and enthalpy of inhibitor binding by using isothermal titration microcalorimetry data. The dissoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 13 publications
1
22
0
1
Order By: Relevance
“…Caffeine is known to activate RyRs and triggering the outflow of Ca 2+ ions [31]. High concentrations or chronic exposure to caffeine may inhibit the activity of adenosine deaminase (ADA) [41] as well as cAMP phosphodiesterase (cAMP PDE) [42]. Maintaining a stable, homeostatic adenosine level in the extracellular space is crucial for D. melanogaster development [20,34].…”
Section: Discussionmentioning
confidence: 99%
“…Caffeine is known to activate RyRs and triggering the outflow of Ca 2+ ions [31]. High concentrations or chronic exposure to caffeine may inhibit the activity of adenosine deaminase (ADA) [41] as well as cAMP phosphodiesterase (cAMP PDE) [42]. Maintaining a stable, homeostatic adenosine level in the extracellular space is crucial for D. melanogaster development [20,34].…”
Section: Discussionmentioning
confidence: 99%
“…Vasorelaxation results in decreased wave reflection indices, whereas vasoconstriction has the opposite effect. As it has been demonstrated, caffeine exerts its main cardiovascular effects through the antagonism of adenosine and the release of catecholamines, both resulting in vasoconstriction (Robertson et al, 1978;Smits et al, 1987;Varani et al, 1999;Corti et al, 2002;Lane et al, 2002;Brodmann et al, 2003;Saboury et al, 2003). In this context, it has been shown that norepinephrine infusion increases augmentation index (Wilkinson et al, 2001;Stewart et al, 2003).…”
Section: Mechanismsmentioning
confidence: 99%
“…Effect of inosine, 12 caffeine, 13 theophyline, 14 acetaminophen, 15 theobromine, 16 as inhibitors on ADA activity has been studied by spectroscopy and calorimetry. The enthalpy, equilibrium and inhibition constants for binding were obtained.…”
Section: Introductionmentioning
confidence: 99%